Overview of temporal soliton transmission on photonic crystal fiber and nanowires - Muhammad Sufi Roslan; Kashif Tufail Chaudhary; Elham Mazalam (Lembaga Studi Pendidikan dan Rekayasa Alam Riau, 2020)
Solitons are nonlinear waves that exhibit persistent propagation in the anomalous dispersion regime. In this article, we demonstrate the generation of soliton pulse in photonic crystal waveguide and nanowire at nonlinear length 6 mm in several photonic crystal waveguides and nanowire including fiberglass, silicon, silica, hollow photonic crystal, and tellurite glass. Optical soliton pulse compression 0.5 ps with increasing order observed in this model. This study reveals the propagation of soliton is feasible at high order mode in silicon nanowire and tellurite glass as compared with normal fiber and photonic crystals.